I'm not putting on that floral gown: Enforcement and resistance of gender expectations for transgender people with cancer. Issue 10 (October 2021) - Alpert, Ash B.; Gampa, Vikas; Lytle, Megan C.; Manzano, Charlie; Ruddick, Roman; Poteat, Tonia; Quinn, Gwendolyn P.; Kamen, Charles S.
Highlights: Decreasing cancer disparities for transgender people requires input from stakeholders. Our qualitative data suggests: Cancer uniquely impacts transgender people. Our qualitative data suggests: Enforcement of gender expectations creates barriers to oncology care. Our qualitative data suggests: Self-advocacy, allyship, and inclusive policies facilitate cancer care. Abstract: Objectives: Understanding barriers to care for transgender people with cancer is necessary to increase oncologic care access. Little has been published regarding the experiences of transgender people with cancer. We sought to explore these experiences, assess barriers to oncologic care, and elucidate potential solutions. Methods: Using an interpretive descriptive approach, we conducted two group interviews with transgender people who had been diagnosed with cancer and one with physicians who treat patients with cancer. Two investigators independently analyzed verbatim transcripts and, together, refined themes, resolving disagreements with consensus. Member checking and peer debriefing were used to confirm and elaborate on findings. Results: Seven people who had been diagnosed with cancer and five physicians who treat people with cancer participated in group interviews. Themes included: (a) experiences with cancer may uniquely impact transgender people; (b) enforcement of clinician and systemic gender expectations creates barriers to cancer care; and (c) resistance to gender expectations may facilitate care. Conclusions: Gender expectations create barriers to oncologic care, which can be resisted by patients, clinicians, and institutions. Implications for practice: Clinicians and institutions should create gender-inclusive oncologic spaces, demonstrate allyship, and support patient autonomy to decrease barriers to care for transgender people with cancer.